Demographics, Comorbidities, and Care-Seeking Intent Among Individuals with Obesity or Overweight Status Using Outpatient AI-Based Virtual Triage - George A. Gellert; Anna Nowicka; Maria Marecka; Gabriel L. Gellert; Tim Price (Telemedicine Reports)
Objective: Compared with persons with normal body mass index (BMI), examine the profile and health care-seeking intent of individuals with obesity/overweight status engaging outpatient artificial intelligence-based virtual triage and care referral (VTCR). Methods: VTCR encounters of patients with high and normal BMI were compared over a 56-month period to assess differences in demographics, clinical risks, symptoms, conditions, triage recommendations, and care intent. Results: In 7,222,363 encounters, 29.6% of patients reported having obesity/overweight status, increasing with age and peaking at 45–59 years (46.4%). Mean age for the high BMI group was 35.2 years and 28.7 years in the normal BMI group. Patients with obesity/overweight status reported noncommunicable diseases twice as frequently, including hypertension (relative risk [RR] 2.6), hypercholesterolemia (RR 2.4), diabetes mellitus (RR 2.4), and asthma (RR 1.4) (p < 0.05). The group of individuals with obesity/overweight status frequently reported musculoskeletal disorders and gastroesophageal reflux, chronic fatigue symptoms, and were up to four times more likely to have hypertension, obstructive sleep apnea, chronic renal disease, chronic heart failure, cholecystolithiasis, and peripheral vascular disease (p < 0.05). Patients with high BMI were slightly more likely to receive triage recommendations for urgent outpatient consultation or emergency department evaluation. Over one-third of patients were uncertain about the appropriate level of care to engage, but this decreased by half (56.6%) following VTCR in both groups. Conclusions: VTCR effectively identified individuals with high BMI and their associated comorbidities. The results suggest that patients with obesity/overweight status utilize health care services at higher rates. VTCR holds promise as a valuable patient engagement, screening, early diagnosis, and health monitoring tool in managing obesity/overweight status in populations.